(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The aim of the study was to evaluate the phytochemical profile, antioxidant and hepatoprotective effects of aqueous (ADPL), ethanol (EDPL), chloroform (CDPL) and petroleum ether (PDPL) extracts of Dendrophthoe pentandra leaves. The total phenolic (TPC) and flavonoid contents (TFC) were determined by using Folin Ciocalteu method and aluminium chloride assay, respectively. Antioxidant effect was assessed by using DPPH radical scavenging, ferric reducing power (FRP) and total antioxidant content (TAC) assay. Hepatoprotective effect was evaluated against CCl4-induced liver toxicity in long evans rats. Among the extracts, EDPL and PDPL had the highest TAC and TFC. EDPL and PDPL showed potent antioxidant effect that exhibited IC50 31.62 ± 4.10 and 24.30 ± 3.45 μg/ml (DPPH), EC50 28.18 ± 4.24 and 39.25 ± 5.20 μg/ml (FRP) and 373.83 ± 9.10, 352.67 ± 10.23, mg/g equivalent of ascorbic acid (TAC), respectively. The CCl4 significantly induced elevation of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), total protein (TP) and bilirubin as well as liver damage (cirrosis, ballooning and necrosis). However, treatment with D. pentandra extracts (200 mg/kg, p.o) significantly counter balanced the toxicity towards the normal animals. The research may direct further advanced studies to find out hepatoprotective compounds. Bangladesh Pharmaceutical Journal 21(2): 71-79, 2018